PELATIHAN TEKNOLOGI PEMANTAUAN KUALITAS AIR PADA KOLAM PENDEDERAN IKAN CANTANG DI HATCHERY D-MARINE AQUACULTURE KOTA TANJUNGPINANG, KEPULAUAN RIAU - Kusuma, Hollanda Arief; Reni, Angga; Margaretha, Juwita; Anggarudin, Anggarudin; Irawan, Henky (LPPM Universitas Andalas, 2024)
The main issue faced by Hatchery D-Marine Aquaculture is the reliance on manual methods for monitoring water quality in grouper fry rearing ponds, which hinders the efficiency and productivity of aquaculture. To address this, the activity implements the concept of precision aquaculture through the application of Internet of Things technology for monitoring. The objective of this activity is to improve water quality monitoring efficiency and fish rearing productivity, and to enhance the partners' understanding of using real-time IoT-based water quality monitoring devices. The methods used include phases of socialization, training, and the implementation of monitoring devices. Socialization was conducted to convey the solution concept, implementation methods, and to build cooperative relationships with the partners. Training was carried out after the monitoring devices were completed, covering device use, installation, and real-time online water quality monitoring. Evaluation of the training results was conducted through pre-tests, post-tests, and questionnaires, indicating an increase in participants' understanding and satisfaction with the training provided. The results show that the application of Internet of Things based water quality monitoring technology within the framework of precision aquaculture has effectively improved fish rearing efficiency and productivity. The partners can monitor pond conditions in real-time, reduce reliance on manual methods, and enhance production outcomes. The conclusion of this activity is that training and technology implementation provide significant benefits to the partners in managing water quality. For program sustainability, it is recommended that the partners continue periodic training and perform regular device maintenance. Ongoing technical support will ensure that the technology can be used optimally and sustainably.